The contribution of executive functions to creativity in children: What is the role of crystallized and fluid intelligence?. (September 2018) - Krumm, Gabriela; Arán Filippetti, Vanessa; Gutierrez, Marisel
Highlights: We provide data about the relationships among intelligence, executive functions and creativity. First study in proposing a SEM model in order to explain the components that predict creative in Spanish-speaking children. Only shifting predicts creativity and, in the presence of this executive function, Gc would not have direct effects. This study has implications for the understanding of the higher-order cognitive mechanisms that explain individual differences in creativity. Abstract: Recent studies have revealed that intelligence and executive functions (EFs) play an important role in creative thinking. However, most research has focused on adult populations, without providing enough clarity as regards the way this complex relationship is manifested in children. The present study broadens and deepens the scope of previous research concerning children, analyzing the relationship between creativity, intelligence and EF, and examining the bond between the three constructs through an Structural Equation Modeling (SEM) approach. A total of 209 8- to 13-year-olds of both sexes (boys n  = 86, girls n  = 123) were administered measures of creativity, crystallized (Gc) and fluid intelligence (Gf) and EFs (i.e., working memory, inhibition and shifting). Correlational analyses revealed associations between all cognitive variables under study. After controlling for the child's level of intelligence, only shifting and inhibition continued to make a significant contribution to creativity. Moreover, SEM results indicated that the effect of Gc on creativity was mediated by shifting. These findings suggest that EFs differently support creativity in children and that shifting is a more powerful predictor of creativity than fluid and crystallized intelligence.